CCN1 secretion and cleavage regulate the lung epithelial cell functions after cigarette smoke - Moon, Hyung-Geun (American Physiological Society, 2014)
Despite extensive research, the pathogenesis of cigarette smoking (CS)-associated emphysema remains incompletely understood, thereby impeding development of novel therapeutics, diagnostics, and biomarkers. Here, we report a novel paradigm potentially involved in the development of epithelial death and tissue loss in CS-associated emphysema. After prolonged exposure of CS, CCN1 cleavage was detected both in vitro and in vivo. Full-length CCN1 (flCCN1) was secreted in an exosome-shuttled manner, and secreted plasmin converted flCCN1 to cleaved CCN1 (cCCN1) in extracellular matrix. Interestingly, exosome-shuttled flCCN1 facilitated the interleukin (IL)-8 and vascular endothelial growth factor (VEGF) release in response to cigarette smoke extract (CSE). Therefore, flCCN1 potentially promoted CS-induced inflammation via IL-8-mediated neutrophil recruitment and also maintained the lung homeostasis via VEGF secretion. Interestingly, cCCN1 abolished these functions. Furthermore, cCCN1 promoted protease and matrix metalloproteinase (MMP)-1 production after CSE. These effects were mainly mediated by the COOH-terminal fragments of CCN1 after cleavage. Both the decrease of VEGF and the elevation of MMPs favor the development of emphysema. cCCN1, therefore, likely contributes to the epithelial cell damage after CS. Additionally, CSE and cCCN1 both stimulated integrin-α(7) expressions in lung epithelial cells. The integrin-α(7) appeared to be the binding receptors of cCCN1 and, subsequently, mediated its cellular function by promoting MMP1. Consistent with our observation on the functional roles of cCCN1 in vitro, elevated cCCN1 level was found in the bronchoalveolar lavage fluid from mice with emphysematous changes after 6 mo CS exposure. Taken together, we hypothesize that cCCN1 promoted the epithelial cell death and tissue loss after prolonged CS exposure.